Strategic marketing problems : cases and comments - Kerin, Roger A.; Peterson, Robert A. 1944- (Upper Saddle River, N.J. : Prentice Hall, 2010)
Provides relevant information and case studies geared toward marketing executives and professionals
Foundations of strategic marketing management -- Financial aspects of marketing management -- Marketing decision making and case analysis -- Opportunity analysis, market segmentation, and market targeting -- Product and service strategy and brand management -- Integrated marketing communication strategy and management -- Marketing channel strategy and management -- Pricing strategy and management -- Marketing strategy reformulation : the control process -- Global marketing strategy.
Includes bibliographical references and indexes.
eng.
Keywords: Marketing -- Case studies; Marketing -- Case studies